The Effect of Black Tea ( (L) Kuntze) on Pediatrics With Acute Nonbacterial Diarrhea - Sareh Doustfatemeh MD; Mohammad Hadi Imanieh MD; Abdolali Mohagheghzade PhD; Mohammad M. Zarshenas PharmD, PhD; Zahra Torkamani MD; Gholamhossein Yousefi MD; Saman Farahangiz MD; Alireza Salehi MD, MPH, PhD (SAGE Publishing, 2017)
We aimed to evaluate the antidiarrheal effect of black tea in pediatric patients with acute nonbacterial diarrhea. This single-blind randomized clinical trial study was performed on 2 to 12-year-old patients, with acceptable criteria for acute nonbacterial diarrhea in Shiraz, Iran. In total, 120 patients took part in this study. Blocked randomization method was used to allocate them into 2 groups of intervention (black tea tablet + standard treatment) and control group (standard treatment; 60 patients in each). Frequency of defecation, volume, and consistency of stool were registered on arrival and 24 hours later. We used χ 2 test, t test, and Mann-Whitney U test. After a 24-hour follow-up, the proportion of patients with formed stool was higher in the intervention group when compared with the control group ( P < .001). There was a significant difference between the mean number of defecations per 24 hours in both groups, after treatment ( P < .001). We found a possible antidiarrheal effect of black tea.